1996
DOI: 10.1021/jp960590g
|View full text |Cite
|
Sign up to set email alerts
|

One-Electron Oxidation Reactions of Some Purine and Pyrimidine Bases in Aqueous Solutions. Electrochemical and Pulse Radiolysis Studies

Abstract: The reduction potentials of some purine and pyrimidine bases and the guanine nucleoside and nucleotide at pH values between 7 and 13 were investigated using the techniques of cyclic voltammetry, differential pulse polarography, and pulse radiolysis. The results clearly show that the lowest reduction potentials, in volts vs NHE, at pH 7 are those of xanthine, 0.88 V, and 1-methylguanine, 1.06 V (NHE). The extrapolated value of guanine is ca. 1.0 V. We also studied the one-electron oxidation reaction of the azid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
87
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 45 publications
16
87
0
1
Order By: Relevance
“…218 It has been suggested that the high ability to conduct holes is developed to protect essential parts of DNA against oxidation by transferring the attacking hole to a less essential part of the genome. Of the four bases guanine is more easily oxidized than the three others ͓E ͑pH 7͔: G 1.04 V, T 1.29 V, A 1.32 V, and C 1.44 V vs. NHE͒ 219,220 and by having long stretches of GC without essential function in the cell and good conductivity, the damaging hole may be transferred to the more easily oxidized part of the genome, and the hole may end by oxidizing guanine to 7,8-dihydro-8-oxoguanine. G is not only the most easily oxidizable base, but its catalytic one-electron oxidation in poly-G sequences is particular fast.…”
Section: Rcoomentioning
confidence: 99%
“…218 It has been suggested that the high ability to conduct holes is developed to protect essential parts of DNA against oxidation by transferring the attacking hole to a less essential part of the genome. Of the four bases guanine is more easily oxidized than the three others ͓E ͑pH 7͔: G 1.04 V, T 1.29 V, A 1.32 V, and C 1.44 V vs. NHE͒ 219,220 and by having long stretches of GC without essential function in the cell and good conductivity, the damaging hole may be transferred to the more easily oxidized part of the genome, and the hole may end by oxidizing guanine to 7,8-dihydro-8-oxoguanine. G is not only the most easily oxidizable base, but its catalytic one-electron oxidation in poly-G sequences is particular fast.…”
Section: Rcoomentioning
confidence: 99%
“…However, a high pH is not favorable for this system, because it elevates the risk of oxidative base damage. [28] Use of LACE-PCR to provide products possessing restriction enzyme termini…”
Section: Photoremoval Of the Npp Group For Further Manipulationmentioning
confidence: 99%
“…通常 认为, 空穴沿着 DNA 链传递是空穴通过鸟嘌呤碱基(G) 而发生的多步短距离跳跃过程 [9] . 在形成 DNA 链的所 有四个碱基中, 由于 G 碱基具有最低的氧化还原电 势 [10] , 因此空穴最终会被 G 碱基捕获, 产生鸟嘌呤自由 3) [15,16] , 因此双链 DNA 中的 G 碱 基被单电子氧化为 G •+ 后, 质子会首先从 G •+ 的 N(1)位 点通过氢键转移到 C 碱基的 N(3)位上, 最终在 C 碱基上 被水分子捕获 [17~19] . 这一脱质子过程的速率常数约为 10 6 到 10 7 s -1 , 完全可以与空穴传递过程竞争, 因而导 致空穴在双链 DNA 中只能传递大约 200 Å [20] .…”
Section: 引言unclassified